0240 Inflammatory Response to Experimentally-Induced Insomnia Symptoms in Healthy Participants. (27th April 2018) - Besedovsky, L; Yang, H; Ciulla, M; Jeffery, M; Mullington, J; Haack, M
Abstract: Introduction: Sleep disturbances as seen in insomnia disorder are associated with increases in inflammatory markers. To investigate whether these inflammatory changes are causally related to the characteristic sleep patterns of insomnia patients (including delayed sleep onset, frequent nocturnal awakenings, early morning awakening), we measured the inflammatory response to a newly developed model of experimentally-induced insomnia symptoms (EIIS) in healthy humans. Methods: Twenty-four healthy humans (age: 27.9 ± 1.2 years; 50% women) participated in a within-subjects study including two 19-day in-hospital stays. During the EIIS condition, three nights with an 8-hour sleep opportunity (2300 - 0700h) were followed by three cycles of three nights with sleep disruption (EIIS nights) and one night of recovery sleep. During EIIS nights, sleep onset was delayed and offset advanced by one hour and sleep time was interrupted by hourly 20-min awakenings. During recovery nights as well as during the control condition, undisturbed sleep was allowed for 8 hours. Lipopolysaccharide (LPS)-stimulated and unstimulated production of interleukin (IL)-6 in monocytes and C-reactive protein (CRP) levels in plasma were measured (together with several other parameters not yet analyzed) in blood collected at 1100h on selected EIIS and recovery nights of each cycle. Results: As expected, the model effectively reduced sleep efficiency and increased sleep onset latency (preliminary polysomnographic analysis in 10 participants). CRP levels and unstimulated IL-6 production in monocytes were reduced in the EIIS condition compared to control (p<0.05). No effect was observed on LPS-stimulated IL-6 production. Conclusion: Inflammatory markers were reduced rather than increased in the EIIS condition. This might indicate that the inflammatory system over-compensates any disturbances induced by the EIIS protocol in our healthy, young participants, conceivably due to a strong counter-regulation by anti-inflammatory substances like cortisol (analysis in progress). This regulation might fail after chronic sleep disruption as seen in insomnia patients. Support (If Any): NIH/NINDS (NS091177) and NIH/UL1 RR02758 and M01-RR-01032 from the National Center for Research Resources to the Harvard Clinical and Translational Science Center.